Simultaneous Displaced Anterior and Posterior Cruciate Ligament Avulsion Fractures After Fall From a Bicycle: A Case Report. Issue 4 (8th October 2022) - Berrian, Kaitlyn M.; Lee, Patrick; Issack, Paul S.
Abstract : Case: We present the case of a 31-year-old man who sustained simultaneous displaced anterior and posterior cruciate ligament (PCL) tibial avulsion fractures after falling from a bicycle. Conclusion: Combined avulsion fractures of the anterior and PCLs is an extremely unusual event and has rarely been reported. The displaced fragments pulled proximally by their respective cruciate ligaments required open reduction and internal fixation to prevent impingement and instability. The patient had excellent clinical and radiographic results after open reduction internal fixation of both fractures.